L'Ardenne & la Meuse; De Ardennen & de Maas; The Ardennes & the Meuse; Die Ardennen & die Maas - Vincent Merckx (Brussel Merckx, 1997)
The land of Ardennes, harsh yet fascinating, has preserved most of its original rugged beauty and its own mysterious character. Now a popular tourist region, the Ardennes group under this name a number of regions which vary a great deal, where rocks have their own special shades and where the villages and rivers all present individual aspects. This infinite variety of forms, colours and seasons is portrayed in this handsome volume with more than 100 colour photographs, many of which are panoramic.
Keywords: Nonfiction; Photography; Travel